ІNTERACTION OF ORAL AND MUSICAL ARTS IN DRAMATIC WORK: SOME THEORETICAL ASPECTS OF A PLAY FUNCTIONING - Олексюк, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Some theoretical aspects of oral and musical arts, their synthesis and functionality in a dramatic work have been studied. The examples of Ukrainian and world drama prove the interdependence of literary and musical images, their organic complementarity, and, finally, their peculiarity in creating plays and performances. The regularities of appearance of certain stylistic dominants of such artistic forms are substantiated, and the methodological possibilities in the study of these ideological and aesthetic phenomena are highlighted.